PERSEPSI ANAK PADA ACARA TELEVISI - Tandiyo Pradekso (Faculty of Social and Political Sciences, Universitas Diponegoro, 2015)
The poor quality of television program available to Indonesian children and the escalating cases of antisocialand delinquency among children are undeniably the hard fact. But linking the two in a causal relationship isa mere speculation that oversimplifying the issue. At the conceptual level in the study of mass communication,there are theories based on the perspective of the limited influence of the mass media. Theories such as those ofKlapper’s phenomenistic, DeFleur’s individual differences and social category, selective processes theory, andSeymour Feshbach’s catharsis theory, are all discouraging the behavioral effect of mass communication. Mediainfluence on children is determined by their comprehension in TV viewing. By about age 8 or 9 (Huston et.al),children are about as accurate as adults in judging whether a television program is presenting fiction or fact.There are arguments on how children perceive the reality out of the television. First, Aletha C. Hustonexplained that perceptions of reality occur on two dimensions: factuality and social realism. Second, Gunter andMcAleer pointed out that children use three categories of television versus real-life comparisons. These include thecategory of the ‘actual’, the ‘possible’, and the ‘impossible’. The third explanation dealt with the way childrenevaluate characters in television programs. Findings revealed that perception on factuality was dominant inprograms such as news, sports, infotainment, talk-show, variety-show, music, and reality-show. Perception ofsocial realism was dominant in cartoons, movies, and soap-operas. Similar to those of factuality, the actualcategory appeared predominantly in news, sports, religion, talk-show, variety-show, music, and reality-show. Thepossible was slightly highlighted in cartoons, movies, and soap-operas. While the impossible also seemeddominant in cartoons, movies, and soap-operas. Conceptually, the 4 children’s favorite characters are the humorof the characters; the strength of the characters; the attractiveness of the characters; and the activity level of thecharacters. Humor was dominant in cartoons, talk-show, and variety-show. Strength was central in sports andmovies, and attractive in infotainment and talk-show. There were no active characters significantly perceived inany television programs.